An overview of magnetorheological polishing fluid applied in nano-finishing of components. Issue 2 (November 2022) - Kumar, Manjesh; Singh Yadav, Hari Narayan; Kumar, Abhinav; Das, Manas
Surface quality is the most crucial factor affecting the product lifespan and performance of any component. Most earlier technologies display accuracy in the micrometre or submicrometre range, surface roughness in the nanometre range, and almost no surface defects in the production of optical, mechanical and electronic parts. Such finishing methods incorporate a magnetic field to control the finishing forces using magnetorheological fluid as the polishing medium. Magnetorheological fluid (MR) consists of ferromagnetic and abrasive particles. It is a type of modern intelligent fluid. An optimum selection of magnetorheological fluid constituents and their volume concentration plays an essential role for the ultra-fine finishing of newly developed engineering products. Rheological characteristics of magnetorheological fluid can change rapidly and effortlessly with the support of an activated magnetic field. Traditional finishing methods are comparatively inferior in finishing complex freeform surfaces, due to the lack of controlling finishing forces and limitations of polishing tool movement over the complex freeform contour of the components. There are different types of processes based on the magnetorheological fluid including magnetorheological finishing, magnetorheological abrasive flow finishing, rotational magnetorheological abrasive flow finishing and ball end magnetorheological finishing. This article discusses the development of different types of magnetorheological-fluid-based finishing processes and their modes of operation. The MR fluid devices developed in the last decade are thoroughly reviewed for their working principles, characteristics and applications. This article also highlights the study of rheological characterization of magnetorheological fluid and its applications in different polishing methods appropriate for finishing various complex freeform components.